Aerobic Oxidation Catalysis with Air or Molecular Oxygen and Ionic Liquids. Issue 9 (15th June 2015) - Gunasekaran, Nanjappan
Abstract Selective aerobic oxidation reactions are most important and challenging transformations in both academic research and the chemical industry. Over the past decade, ionic liquids have gained recognition in the context of green organic synthesis as they are not only possible environmentally benign solvents but also serve as a liquid support or catalyst in various chemical processes. Hence, in recent years, there has been a growing interest in the development of aerobic oxidation reactions combined with ionic liquids and molecular oxygen or air which has led to the improvement of green catalytic systems capable of achieving high selectivity and yields. Thus, this review aims to give an overview of the most important advances made by in the field of aerobic oxidation reactions in combination with either molecular oxygen or air as oxidant and ionic liquids as solvent, liquid support or catalyst.